Implementasi Kebijakan Pengurangan Penggunaan Kantong Plastik di Kabupaten Siak : (Studi Pada Kawasan Objek Wisata, Pasar Tradisional dan Kantor Pemerintah) - Novela Lestari Novela Lestari; Hasim As'ari (UIR Press, 2022)
This research was conducted with the aim of knowing and analyzing the implementation of policies to reduce the use of plastic bags and find out what are the inhibiting factors of implementing policies to reduce the use of plastic bags in tourist attractions, traditional markets and government offices in Siak Regency. The implementation theory used is the MSN-Approach implementation theory from Yulianto Kadji (2015) which sees the implementation of three approaches, namely the mentality approach, the systems approach and the networking approach. The method used in this research is a qualitative research method. The required data, both primary and secondary data, were obtained by means of observation, interviews and documentation. The results of this study indicate that: first, the implementation of the policy to reduce the use of plastic bags in Siak Regency has not run optimally. Second, the inhibiting factors in implementing the policy are not comprehensive socialization, the presence of street vendors who are not orderly, there is no sanction for violators, and people's habits are difficult to change.